Accounting for Multinational Enterprises. (Book Review). - Meyer, Philip E.; Fantl, Irving L. (The Accounting Review, 1981)
Abstract Reviews the book "Accounting for Multinational Enterprises," edited by Dhia D. AlHashim and James W. Robertson.